2016
DOI: 10.1371/journal.pone.0150240
|View full text |Cite
|
Sign up to set email alerts
|

Liver Transcriptome Analysis of the Large Yellow Croaker (Larimichthys crocea) during Fasting by Using RNA-Seq

Abstract: The large yellow croaker (Larimichthys crocea) is an economically important fish species in Chinese mariculture industry. To understand the molecular basis underlying the response to fasting, Illumina HiSeqTM 2000 was used to analyze the liver transcriptome of fasting large yellow croakers. A total of 54,933,550 clean reads were obtained and assembled into 110,364 contigs. Annotation to the NCBI database identified a total of 38,728 unigenes, of which 19,654 were classified into Gene Ontology and 22,683 were f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 38 publications
7
21
0
Order By: Relevance
“…The optimum water temperature for the growth of large yellow croaker is 18–25 °C. The large yellow croaker cannot tolerate high temperatures above 34 °C and low temperatures below 7 °C; the fish will reduce food intake when seawater temperatures are above 28 °C or below 14 °C [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…The optimum water temperature for the growth of large yellow croaker is 18–25 °C. The large yellow croaker cannot tolerate high temperatures above 34 °C and low temperatures below 7 °C; the fish will reduce food intake when seawater temperatures are above 28 °C or below 14 °C [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…This result was further corroborated by Nile Red staining of neutral lipid droplets, which showed increased accumulation in the visceral adipocytes after exogenous feeding. In adult fish, the endogenous reserves of lipids meet the metabolic demands of the fish during fasting [ 42 , 43 ] and supply energy for exercise [ 44 ] and cold acclimation [ 45 ]; thus, these reserves are essential for the survival of fish throughout their life cycle. Our data verified that lipid deposition in zebrafish larvae commences with the mouth-opening stage.…”
Section: Discussionmentioning
confidence: 99%
“…The result showed eight genes were significantly attenuated in the absence of exogenous nutrition, indicating that exogenous nutrition is an important activator of the MHC pathway. Furthermore, we compared the DEGs involved in the MHC pathways identified in our study with those in the response to long term starvation in the adult large yellow croaker ( Larimichthys crocea ) [ 42 ]. The inconsistent result was observed that the latter not alter the gene expression level associated with MHCs pathway under starvation ( Table S6 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the situation of limited energy supply, the organisms adapt by adjusting the rate of protein synthesis and degradation. A study showed that protein synthesis in the endoplasmic reticulum was significantly decreased and proteolysis was significantly increased in the liver of yellow croaker after 21 days of fasting (Qian et al, 2016). The increased expression of aspartate aminotransferase that participates in malateaspartate shuttle in the fasted A. davidianus liver indicates that prolonged fasting induces tissue protein degradation, thus promoting gluconeogenesis of glucogenic amino acids.…”
Section: Prolonged Fasting Is Accompanied By Increase Of Proteolysis mentioning
confidence: 99%
“…For the South African clawed toad Xenopus laevis, its liver glycogen levels were reduced by 80-90% after 12 months of starvation at 20 • C (Merkle and Hanke, 1988). For other vertebrates, several studies showed that genes involved in ketogenesis, gluconeogenesis, and fatty acid beta-oxidation, were up-regulated in liver of chicken after 16 h of starvation (Desert et al, 2008), in liver of mice after 24 h of starvation (Kinouchi et al, 2018;Rennert et al, 2018), in liver of fishes after 21 days of starvation (Drew et al, 2008;Qian et al, 2016). Compared to other vertebrates, the hypogean salamanders exhibited remarkable resistance to long periods of food deprivation, this may be due to the remarkable accumulation of lipid and glycogen deposits in the liver, and glycogen level maintenance during food deprivation.…”
Section: Introductionmentioning
confidence: 99%